Can Land Redistribution Aid in Reducing Poverty and Inequality in South Africa? - More, Itumeleng (University of the Witswatersrand, Johannesburg, 2023)
Land allocation has been a thorny issue in South Africa. Post-democracy, the ANC government promised to redistribute land to poor citizens with the main aim of eradicating poverty, ensuring employment of citizens, and enhancing economic development in the nation. This paper looks at different land redistribution approaches that can been used in land reforms with the main focus on the market-led approach and government-led approach. A systematic review has been utilized in the research to identify land reform processes in South Africa. Out of the twelve reviewed articles, eight indicate that land redistribution had a positive impact on addressing poverty, unemployment, and economic development. The articles also indicate that market-led land distribution did not achieve its intended objectives. The paper concludes that there is a need for comprehensive government intervention in land-redistribution and -allocation in South Africa.
A dissertation submitted at University of the Witwatersrand School of Economics and Finance Applied Development Economics Masters Programme (CCA01) Research Report (ECON7052A)
Keywords: Land allocation; Post-democracy; ANC government; Economic developmen; South Africa; Land Redistribution; Poverty and Inequality; UCTD; SDG-1: No poverty